Підходи до формування адаптивної організаційної структури в системі управління будівельно-інвестиційними проектами - Письменний, О. М. (Ways to Improve Construction Efficiency, 2012)
Methodological approaches to organizational structure formation of corporate unions are substantiated in the article. Variants of project groups inclusion in organizational structure of enterprise at different organizational forms are offered.